Chinese power-grid financial capacity based on transmission and distribution tariff policy: A system dynamics approach. (October 2019) - Wang, Yongli; Zhang, Fuli; Zhang, Yuanyuan; Wang, Xiaohai; Fan, Lisha; Song, Fuhao; Ma, Yuze; Wang, Shuo
Abstract: With reforms, the Chinese power grid is transitioning to a more dynamic and competitive power market. Transmission and distribution tariff policies have changed the profit model and influence the financial capacity of the Chinese power-grid companies. This study analyzes the specific content of the reform, the calculation related to each component of power-grid financial capacity, and the interaction and feedback characteristics among the components. On this foundation, we establish a financial capacity model using the system dynamics theory. Taking a power-grid company as a case to undertake empirical and sensitivity analyses, we put forward management strategies and policy recommendations. Highlights: Discuss policy implications with an explicit concern on investment capacity issue. Define the interaction and feedback characteristics between the components of investment capacity. Establish a system dynamics calculation model of power grid investment capacity. The investment capacity of power grid companies will keep growing in the future.